2018
DOI: 10.1186/s40880-018-0325-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an endoscopic images‐based deep learning model for detection with nasopharyngeal malignancies

Abstract: BackgroundDue to the occult anatomic location of the nasopharynx and frequent presence of adenoid hyperplasia, the positive rate for malignancy identification during biopsy is low, thus leading to delayed or missed diagnosis for nasopharyngeal malignancies upon initial attempt. Here, we aimed to develop an artificial intelligence tool to detect nasopharyngeal malignancies under endoscopic examination based on deep learning.MethodsAn endoscopic images-based nasopharyngeal malignancy detection model (eNPM-DM) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 40 publications
0
76
0
Order By: Relevance
“…Of the 69 studies, 25 studies did an out-of-sample external validation and were therefore included in a meta-analysis. 21,28,30,34,[36][37][38][39]43,[53][54][55][56]61,[65][66][67]70,73,74,79,81,90,91,99 In line with the aims of this review, all eligible studies were included regardless of the target condition. The meta-analysis therefore included diagnostic classifications in multiple specialty areas, including ophthalmology (six studies), breast cancer (three studies), lung cancer (two studies), dermatological cancer (three studies), trauma and orthopaedics (two studies), respiratory disease (two studies), Of these 25 studies, only 14 used the same sample for the out-of-sample validation to compare performance between deep learning algorithms and health-care professionals, with 31 contingency tables for deep learning algorithm performance and 54 tables for healthcare professionals (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 69 studies, 25 studies did an out-of-sample external validation and were therefore included in a meta-analysis. 21,28,30,34,[36][37][38][39]43,[53][54][55][56]61,[65][66][67]70,73,74,79,81,90,91,99 In line with the aims of this review, all eligible studies were included regardless of the target condition. The meta-analysis therefore included diagnostic classifications in multiple specialty areas, including ophthalmology (six studies), breast cancer (three studies), lung cancer (two studies), dermatological cancer (three studies), trauma and orthopaedics (two studies), respiratory disease (two studies), Of these 25 studies, only 14 used the same sample for the out-of-sample validation to compare performance between deep learning algorithms and health-care professionals, with 31 contingency tables for deep learning algorithm performance and 54 tables for healthcare professionals (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“… We use the TNM classification of malignant tumors from the union for international cancer control 22…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this study, we demonstrate the diagnostic ability of an AI‐based diagnosing system to detect pharyngeal cancer from EGD images. Although there are two studies about AI diagnosis of pharyngeal cancer, in which otolaryngologists demonstrated the use of AI with images in per‐nasal endoscopy,21,22 no published study has demonstrated the usefulness of AI diagnosis to detect SPC by EGD.…”
Section: Introductionmentioning
confidence: 99%
“…To make this happen, one needs to build convolutional neural networks (CNN), identify the features of the image to be extracted, and finally identify the tumor using deep learning algorithms. Li et al [80] developed an endoscopic image-based deep learning model that had 88% accuracy. This was achieved using 28,966 images from 7951 subjects over 8 years to form the test set for an endoscopic image-based NPC detection model.…”
Section: Advanced Computing Technologiesmentioning
confidence: 99%